2016
DOI: 10.3133/sir20155148
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in groundwater of Licking County, Ohio, 2012—Occurrence and relation to hydrogeology

Abstract: These professionals contributed to (1) planning and oversight of the project, and (2) compilation and review of multiagency arsenic-related data for a Web site (http://ArsenicInOhioGroundwater.info). The author would also like to thank Chad Brown and his staff at the Licking County Health Department for: (1) collection of water samples for analysis of arsenic during routine well inspection activities, and (2) efforts related to planning and implementation of the Test Your Well workshops. The author also apprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…6. This is consistent with other research where arsenic was found to be associated with iron (Welch et al 2000;Thomas 2016). Correlations were also observed between arsenic and copper and arsenic and zinc, although these correlations were considerably lower.…”
Section: Other Metals In Soilsupporting
confidence: 82%
See 2 more Smart Citations
“…6. This is consistent with other research where arsenic was found to be associated with iron (Welch et al 2000;Thomas 2016). Correlations were also observed between arsenic and copper and arsenic and zinc, although these correlations were considerably lower.…”
Section: Other Metals In Soilsupporting
confidence: 82%
“…A USGS study performed in Licking County, Ohio, found that elevated arsenic concentrations in groundwater are associated with strongly reducing conditions that promote dissolution of arsenic (Thomas 2016). Although redox levels are not reported in SSURGO, the database does include some data regarding the frequency and duration of ponding.…”
Section: Pondingmentioning
confidence: 99%
See 1 more Smart Citation
“…1). These are areas where arsenic in groundwater has been investigated or documented by Dumouchelle (1999), Ohio Department of Health (1999), Shindel and others (2000), Miami Conservancy District (2011), Thomas andothers (2005, 2008), and Thomas (2016). The hydrogeology of the Great Miami River Basin has been summarized by Debrewer and others (2000) and the Miami Conservancy District (2013).…”
Section: Description Of Study Areamentioning
confidence: 99%
“…A recent study of 168 domestic wells in Licking County found that almost 1 in 8 wells had arsenic concentrations that exceeded the U.S. Environmental Protection Agency Maximum Contaminant Level of 10 parts per billion (Thomas, 2016; U.S Environmental Protection Agency, 2012). Elevated arsenic concentrations were associated with geologic characteristics and geochemical conditions that exist in the western part of the county.…”
Section: Groundwater Arsenic and Methane In Groundwater Of Ohiomentioning
confidence: 99%